ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EMISI KARBONDIOKSIDA DI NEGARA INDUSTRI BARU TAHUN 2000-2020 - Tri Setyo, Septa; Nur Sarfiah, Sudati; Aji Prakoso, Jalu (Jendela Inovasi Daerah, 2024)
Global warming is a very serious issue in this era of globalization and there is always news all over the world. One of the causes of global warming is an increase in greenhouse gases (GHG). Of the various types of greenhouse gases (GHG), carbon emissions (CO2) are the most important source of problems. This is because carbon emissions make the highest contribution, namely 76 percent, to changes in global warming. Newly Industrialized Countries are one of the groups of countries that contribute the highest levels of CO₂ emissions in the world, which have continued to increase every year over the last 21 years. This research aims to analyze the factors that influence carbon dioxide emissions in New Industrial Countries from 2000 to 2020. The type and source of data used is based on the IPAT (Impact-Population-Affluence-Technology) model with quantitative descriptive methods, using data secondary data in the form of time series for 21 years and cross section using 10 countries in the New Industrial Countries. The results of this research show that the variables of population growth rate, urbanization, per capita income, and trade openness have a positive and significant impact on the level of carbon dioxide (CO₂) emissions in Newly Industrialized Countries in 2000-2020. Meanwhile, the variable number of internet users has a negative and significant effect on the level of carbon dioxide (CO₂) emissions in New Industrial Countries in 2000-2020.